QRIS Usage and Transaction Efficiency among Culinary Micro-Enterprises in Kendari City - Rachmawati, Rachmawati; Pratama, Muhammad Faried (LifeSciFi, 2026)
The development of digital payment systems has encouraged micro-enterprises to adopt non-cash transaction methods that offer greater efficiency. This study aims to examine the effect of QRIS usage on transaction efficiency from the perspective of micro-enterprises in the culinary sector in Kendari City. The study employs a quantitative explanatory approach using a survey method involving 84 micro-enterprise owners who have used QRIS for at least six months. Data were collected through structured questionnaires and analyzed using simple linear regression. The results indicate that QRIS usage has a positive and significant effect on transaction efficiency. Increased utilization of QRIS is proven to accelerate transaction processes, reduce operational costs associated with cash handling, and improve the accuracy of financial record-keeping. The coefficient of determination shows that QRIS usage explains a substantial proportion of the variance in transaction efficiency. These findings highlight that QRIS functions not only as a digital payment instrument but also as a mechanism to enhance operational efficiency among micro-enterprises in the culinary sector. This study provides empirical evidence that enriches the literature on digital payment systems in the context of micro-enterprises, particularly in Eastern Indonesia, and offers practical insights for business actors and policymakers in promoting payment system digitalization.